2016
DOI: 10.1038/mtna.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Effective Prevention of Liver Fibrosis by Liver-targeted Hydrodynamic Gene Delivery of Matrix Metalloproteinase-13 in a Rat Liver Fibrosis Model

Abstract: Liver fibrosis is the final stage of liver diseases that lead to liver failure and cancer. While various diagnostic methods, including the use of serum marker, have been established, no standard therapy has been developed. The objective of this study was to assess the approach of overexpressing matrix metalloproteinase-13 gene (MMP13) in rat liver to prevent liver fibrosis progression. A rat liver fibrosis model was established by ligating the bile duct, followed by liver-targeted hydrodynamic gene delivery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…In our study, we further confirmed this antifibrotic effect by quantitative image analysis of liver tissue which is more effective than qualitative and semiquantitative methods [19]. Both Nilotinib and stem cell-conditioned media showed antifibrotic effect, but there was no significant difference between the Nilotinib and stem cell-conditioned medium treatment against CCl 4 -induced liver fibrosis in rats.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our study, we further confirmed this antifibrotic effect by quantitative image analysis of liver tissue which is more effective than qualitative and semiquantitative methods [19]. Both Nilotinib and stem cell-conditioned media showed antifibrotic effect, but there was no significant difference between the Nilotinib and stem cell-conditioned medium treatment against CCl 4 -induced liver fibrosis in rats.…”
Section: Discussionsupporting
confidence: 74%
“…Then, slides were stained with Masson trichrome as routine connective tissue stain. Images were captured from each section randomly, and a quantitative analysis of fibrotic area was performed using the ImageJ software (version 1.6.0_20, National Institutes of Health, Bethesda, MD) as previously reported [19].…”
Section: Hepatic Histopathological Evaluationmentioning
confidence: 99%
“…Liver-targeted hydrodynamic delivery of MMP-13 gene could be useful in prevention of liver fibrosis. 90 …”
Section: Special Attributes Of Specific Mmpsmentioning
confidence: 99%
“…Such genetic alterations are quite common in many human genetic disease 25,26 and our strategy can be applicable to human germline gene therapy to correct disease causing mutations. Insertion of long sequences will be also useful as one of the gene therapy strategies based on the addition of a functional gene 27 . Considering that human germline gene therapy will often be coupled with ex vivo handling of embryos, including an in vitro cell culture step that could cause 20 epigenetic changes of gene expression and affect fetal development 28,29 , i-GONAD, which does not require ex vivo handling or sacrifice of GONAD-treated females, can offer a highly promising approach as a human germline gene therapy tool in the future.…”
Section: Discussionmentioning
confidence: 99%